RESEARCHING OF MEAT AND FAT COLOUR AND MARBLING IN BEEF - A. B. Lisitsyn; I. V. Kozyrev (Теория и практика переработки мяса)
The studies of meat and fat colour and marbling in Longissimus dorsi of different cattle — beef-producing (Aberdeen-Angus,Herefordbreeds) and dual-purpose (Simmental, Black-and-white breeds) — allowed to define groups by the colour values according to Lab international colour model. Measurements were performed 24 hours post-mortem between 12th and 13th ribs. It was found that different ranges of meat colour differed primarily in L* (lightness) and a* (redness) values, while b* (yellowness) values did not significantly differ. The highest differentiation between ranges of fat colour was noted in b* values, whereas L* and a* slightly differed. Moreover, visual assessment of beef marbling by four grades (small, moderate, good, and rich) and instrumental (microstructural) analysis using a computer image analysis system were carried out. The morphometric study of marbling was conducted in accordance with the principles of system quantitative analysis. To perform quantitative measurements, object analysis parameters (area) were specified. Both automatic and manual measurements of specified parameters were used. The study of Longissimus dorsi marbling established high agreement between visual and instrumental evaluations of marbling.